2008
DOI: 10.1021/ja7114426
|View full text |Cite
|
Sign up to set email alerts
|

Nickel-Catalyzed Decarbonylative Addition of Phthalimides to Alkynes

Abstract: An intermolecular nickel-catalyzed addition reaction has been developed where N-arylphthalimides react with alkynes to afford substituted isoquinolones. A mechanistic rationale is proposed, implying nucleophilic attack of Ni(0) to an amide as the primary step of the catalytic cycle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
87
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(87 citation statements)
references
References 51 publications
0
87
0
Order By: Relevance
“…C−N Bond Cleavage via Oxidative Addition.The direct oxidative addition of the low-valent transition metals into an amide C−N bond generating the active C−M−N species provides a good strategy to cleave the amide C−N bond. The Ni-catalyzed decarbonylative addition of Narylphthalimides 225 to alkynes was achieved to afford various isoquinolin-1(2H)-ones 226 (Scheme 66) 201. In this process, the cleavage of an amide C−N bond in 225 is effected by oxidative addition to afford intermediate 227.…”
mentioning
confidence: 99%
“…C−N Bond Cleavage via Oxidative Addition.The direct oxidative addition of the low-valent transition metals into an amide C−N bond generating the active C−M−N species provides a good strategy to cleave the amide C−N bond. The Ni-catalyzed decarbonylative addition of Narylphthalimides 225 to alkynes was achieved to afford various isoquinolin-1(2H)-ones 226 (Scheme 66) 201. In this process, the cleavage of an amide C−N bond in 225 is effected by oxidative addition to afford intermediate 227.…”
mentioning
confidence: 99%
“…Pioneering reports by the research groups of Miura and Satoh, [2] Fagnou, [3] and Jones [4] revealed that particularly rhodium catalysts enabled effective dehydrogenative annulation reactions of alkynes through chelation assistance, [5,6] which have set the stage for very recently developed rhodium-catalyzed isoquinolone [7] syntheses.[8] On the contrary, the use of less-expensive ruthenium [9] catalysts for oxidative annulations through cleavage of C À H bonds has thus far not been reported. During studies on oxidative ruthenium-catalyzed homodehydrogenative arylations, [10] we observed unprecedented ruthenium-catalyzed direct annulations of alkynes [11] through the chemo-and site-selective functionalization of both C À H and N À H bonds, and we wish to disclose our results herein.…”
mentioning
confidence: 99%
“…They revealed that [RuCl 2 ( p ‐cymene) 2 ] (2.5 mol %) alone can efficiently catalyze the reaction in a similar ring‐opening/alkyne insertion manner. An interesting decarbonylative ring‐opening/alkyne insertion reaction of phthalimides by nickel catalysis was also reported by Kurahashi and Matsubara . The reaction proceeded through C(acyl)−N bond cleavage followed by decarbonylation and alkyne insertion.…”
Section: Carbon–carbon Bond Forming Reactionsmentioning
confidence: 75%
“…[42] They revealed that [RuCl 2 (p-cymene) 2 ]( 2.5 mol %) alone can efficientlyc atalyze the reaction in as imilar ring-opening/alkyne insertionm anner.A ni nteresting decarbonylative ring-opening/ alkynei nsertion reaction of phthalimides by nickel catalysis was also reported by Kurahashi and Matsubara. [43] The reaction proceeded through C(acyl)ÀNb ond cleavage followed by decarbonylation and alkyne insertion. Notably,i nvestigation of the substituent effects on the nitrogen atom revealed that phthalimide substrate requires an electron-deficient group, such as pyridine, pyrrole, pyrazine, and pentafluorobenzene.…”
Section: Ring-opening and Alkyne/alkene Insertionmentioning
confidence: 99%